(untitled) (Journal of Small Business Strategy (archive only), 1999)
The limited resources of small businesses often present unique challenges when the companies try to internationalize. This paper examines the decision to enter the global arena from the viewpoint of firms who already are there. The results of a survey of such companies indicate that changes in the external situation often overcome internal reservations firms might have about internationalizing. Survey participants identify issues related to risk management and the assignment of responsibility for international operations as key areas of concern, and they suggest "coping strategies" for small businesses thinking about doing business overseas.